Photophysical Characterization of Green and Blue Emitting Quantum Dots and Their Application in Qd-Leds - Özgüler, Şahika; Varlıklı, Canan (01. Izmir Institute of Technology, 2020)
QLED device construction and characterization studies were carried out in which QD nanoparticles synthesized within the scope of TÜBİTAK project no 115F616, and were used as emission layer. By examining the photo-physical and morphological properties of films prepared with the use of quantum dot (QD) nanoparticles, quantum dot light emitting diodes (QLEDs) which are one of the fields of molecular electronics, were applied as an emission layer using the spin coating technique from wet coating processes. The photo-physical and morphological characterizations of the solution and film phase of blue and green emitted QD nanoparticles were made. For the QDs, the concentration difference in the solution phase was characterized and its effects on film properties were investigated. It has been determined that the increase in concentration does not have a dramatic effect on photo-physical properties but seriously affects film thickness and surface roughness. In this case, performance of blue and green light emitting quantum dot diodes (QLED) prepared by the spin-coating technique, where each QD film is used as the emission layer, have been investigated.

115F616 nolu TÜBİTAK projesi dahilinde senezlenen QD nanoparçacıklarının emisyon katmanı olarak kullanıldığı QLED aygıt yapım ve karakterizasyon çalışmaları yapılmıştır. Kuantum nokta (QD) nanoparçacıklarının kullanımı ile hazırlanan QD filmlerinin fotofiziksel ve morfolojik özellikleri incelenerek, moleküler elektronik uygulama alanlarından biri olan quantum noktacık ışık yayan diyotlarda (QLEDler), ıslak kaplama süreçlerinden dönü kaplama tekniği kullanılarak emisyon katmanı olarak uygulamaları yapılmıştır. Mavi ve yeşil emisyon yapan QD nanoparçacıklarının çözelti ve film fazına ait fotofiziksel, ve morfolojik karakterizasyonları yapılmıştır. QD için çözelti fazındaki konsantrasyon farkı karakterize edilmiş ve film özelliklerine etkileri incelenmiştir. Konsantrasyon artışının fotofiziksel özellikler üzerinde dramatik bir etkisinin olmadığı ancak film kalınlığı ve yüzey pürüzlülüğünü ciddi oranda etkilediği belirlenmiştir. Her bir QD filminin emisyon katmanı olarak kullanıldığı dönü kaplama tekniği ile hazırlanan mavi ve yeşil ışık yayan quantum noktalardan oluşan diyotların (QLED) performans incelemeleri yapılmıştır.
Yeşil ve Mavi Işıma Yapan Kuantum Parçacıklarının Fotofiziksel Karakterizasyonu ve Qd-led Uygulamaları
Includes bibliographical references (leaves. 74-105)
Text in English; Abstract: Turkish and English
Thesis (Master)--Izmir Institute of Technology, Photonics, Izmir, 2020
Keywords: Quantum dots; QD nanoparticles; QLEDs; Light emitting diodes